Examining patient and professional perspectives in the UK for gene therapy in haemophilia. Issue 4 (19th April 2022) - Woollacott, Ione; Morgan, George; Chowdary, Pratima; O'Hara, Jamie; Franks, Bethany; van Overbeeke, Eline; Dunn, Nicola; Michelsen, Sissel; Huys, Isabelle; Martin, Antony; Cawson, Matthew; Brownrigg, Jack; et al.
Abstract: Introduction: With the development of gene therapy for people with haemophilia (PWH), it is important to understand how people impacted by haemophilia (PIH) and clinicians prioritise haemophilia treatment attributes to support informed treatment decisions. Objective: To examine the treatment attribute preferences of PIH and clinical experts in the United Kingdom (UK) and to develop a profile of gene therapy characteristics fit for use in future discrete choice experiments (DCEs). Methods: Semi‐structured interviews were conducted with PIH ( n = 14) and clinical experts ( n = 6) who ranked pre‐defined treatment attributes by importance. Framework analysis was conducted to identify key themes and treatment attributes; points were allocated based on the rankings. Synthesis of results by a multidisciplinary group informed development of a profile of gene therapy characteristics for use in future research. Results: Key themes identified by PIH and clinical experts included patient relevant features and the importance of 'informed decision making'. The six top‐ranked treatment attributes were 'effect on factor level' (79 points), 'uncertainty regarding long‐term risks' (57 points), 'impact on daily life' (41 points), 'frequency of monitoring' (33 points), 'impact on ability to participate in physical activity' (29 points), and 'uncertainty regarding long‐term benefits' (28 points). The final treatment characteristics were categorised as therapeutic option, treatment effectiveness, safety concerns, impact on self‐management and quality of life (role limitations). Conclusion: We identified several gene therapy characteristics important to PIH and clinicians in the UK. These characteristics will be used in a future DCE to further investigate patient preferences for gene therapy.